Multiple analyses of various factors affecting the plantlet regeneration of Picea mongolica (H. Q. Wu) W.D. Xu from somatic embryos - Jia Yan (Nature Portfolio, 2021)
Abstract Picea mongolica, a native species with excellent industrial wood quality and strong sand-fixing capacity, may be utilized in construction of urban green spaces in arid areas in China. However, now the sustainability of the ecosystems where this species grows is at serious risk due to a lack of natural regeneration. In this study, we developed an efficient regeneration system and comprehensively analyzed various factors affecting somatic embryogenesis (SE) using zygotic embryos as explants. We identified the optimal plant growth regulators (PGRs) performance and the best donor trees (k81) for the generation of somatic embryos (SEMs). Additionally, we confirmed that the positive developmental window of SEMs initiation was at the end of July to early August, which is when zygotic embryos was at the late embryogeny. In this time period, specific transcripts associated with the regulation of epigenetic modifications, plant hormone-related genes, and embryonic development-related transcription factors play important roles for early SEMs initiation. These results may provide a valuable resource for vegetative propagation of Picea mongolica. Our results may help to establish a reliable protocol for plantlet regeneration, which may facilitate urban greening applications and industrialization in arid areas.